Development of a pictural test instrument to measure deaf children’s knowledge of sexual violence prevention - Andily Aprilia Rahmawati; Budi Susetyo; Dhea Lutvia; Winny Cahyani Aulia (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
The purpose of this study is to create a pictural instrument test for measuring sexual abuse prevention knowledge in deaf children. The research adopts a quantitative approach utilizing descriptive methods. The population in this study consisted of deaf students who could read and communicate in two ways. The sampling method used is convenience sampling of as many as 66 deaf students. The findings reveal that the instrument exhibits strong validity and reliability. The instrument consisted of 39 attitudinal items and was tested using Explanatory Factor Analysis (EFA) to refine the instrument's accuracy and consistency. The factor analysis process identified 25 suitable items, forming 8 distinct factors based on four key aspects: appropriate and inappropriate touching, safety rules for children, rejecting unwanted sexual advances, and reporting child sexual abuse to trusted adults. The instrument can be a tool to develop targeted strategies, policies, and programs to protect the communities. It is advised that further research be pursued to establish broader validation for this assessment tool while providing thorough justification for the accompanying manual detailing deaf children's knowledge of preventing sexual violence.